Fabrication And Characterization Of Ingan Based Solar Cell: From Material To Device - Yusof, Ahmad Sauffi (2024)
Indium gallium nitride (InGaN) material system has emerged as a promising candidate for high-efficiency solar cells due to its exceptional intrinsic properties. However, developing InGaN-based solar cells faces several challenges, including needing a p-doped layer and producing high-quality indium-rich InGaN alloy. This study explores innovative strategies to overcome these challenges, focusing on the practical development of thick InxGa1-xN-based Schottky solar cells, from material growth to device characterization.